2017
DOI: 10.1007/s11748-017-0874-x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic aortic aneurysm: unlocking the “silent killer” secrets

Abstract: Thoracic aortic aneurysm (TAA) is an increasingly recognized condition that is often diagnosed incidentally. This review discusses ten of the most relevant epidemiological and clinical secrets of this disease; (1) the difference in pathogenesis between ascending and descending TAAs. TAAs at these two sites act as different diseases, which is related to the different embryologic origins of the ascending and descending aorta. (2) The familial pattern and genetics of thoracic aneurysms. Syndromic TAAs only explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
74
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 104 publications
0
74
0
1
Order By: Relevance
“…1 therein. Even though it has been shown that the risk of rupture and dissection of aneurysms increase significantly at sizes larger than 6 cm for the thoracic aorta [26], this criterion is in contradiction with the observation that aneurysms can rupture or dissect at any diameter [11,98,154,97,117], and it ignores the more complex relationships between the rupture and the material properties such as the heterogeneity of tensile strength in the wall of aortic aneurysms [149]. Clinicians need more reliable tools to assess the risk of intervention versus the risk of rupture, as the maximum diameter criterion can underestimate the rupture risk of smaller aneurysms, and overestimate it for the larger ones.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…1 therein. Even though it has been shown that the risk of rupture and dissection of aneurysms increase significantly at sizes larger than 6 cm for the thoracic aorta [26], this criterion is in contradiction with the observation that aneurysms can rupture or dissect at any diameter [11,98,154,97,117], and it ignores the more complex relationships between the rupture and the material properties such as the heterogeneity of tensile strength in the wall of aortic aneurysms [149]. Clinicians need more reliable tools to assess the risk of intervention versus the risk of rupture, as the maximum diameter criterion can underestimate the rupture risk of smaller aneurysms, and overestimate it for the larger ones.…”
Section: Introductionmentioning
confidence: 95%
“…Aortic aneurysms are local dilatations of the aorta, typically more than 50% of the normal diameter [41]. The underlying mechanisms leading to aneurysm formation differ between the ascending aorta and the descending thoracic aorta [117], as well as between the thoracic and the abdominal aorta [33,116,14] due to different embryonic origins of the cells involved in the remodeling process. The aneurysms in the ascending aorta are usually not accompanied by atherosclerosis, whereas in the descending thoracic and the abdominal aorta it is a common finding [57].…”
Section: Introductionmentioning
confidence: 99%
“…Body surface area is a primary determinant of thoracic aortic size, which increases in diameter with the physiological demands that accompany normal growth throughout childhood and into adult life 2 . Extremes in thoracic aortic diameter can manifest in clinically significant disease ranging from thoracic aortic dilation or aneurysm which may be asymptomatic until the occurrence of rupture or dissection [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…TAA mainly occurs after the age of 60, and male patients occupy 80% of TAA cases [ 2 , 3 ]. Most of the TAA cases are caused by the deterioration of atherosclerosis, and a few cases are caused by syphilis [ 3 , 4 ]. Meanwhile, surgical treatment has become the most effective therapy for TAA.…”
Section: Introductionmentioning
confidence: 99%